Survey of the deterministic network - Tao HUANG; Shuo WANG; Yudong HUANG; Yao ZHENG; Jiang LIU; Yunjie LIU (Tongxin xuebao, 2019)
The current Internet faces a huge increase in video traffic and industrial machine applications,causing a lot of congestion and packet delays.Besides,many network applications,such as industrial Internet,telemedicine,driverless,VR games,etc,require a latency from 1 to 10 milliseconds and jitters within microsecond.But traditional network can only reduce the end-to-end latency to tens of milliseconds.Under this background,how to transit from “best effort” to“punctuality,accuracy”,controlling the end-to-end delay has become a hot field of global network research.The application scenarios and requirements of the deterministic network were introduced，and the main research results of the current parties were described as well as the trend of development and core issues were summarized.It hopes to provide a reference and help for the research in this field.